Remain or return? The effect of social network and engagement on settlement intentions among high skilled migrants in Northeast China - Wenbin Wang; Xiaohan Li (PLoS ONE, 2025)
China is transitioning from an immigrant-exporting country to an immigrant-importing country. To attract and retain global, it is necessary to analyze the factors influencing the settlement intentions of high skilled migrants to formulate policy support and tailor the management of transnational communities to their characteristics. This study used the Changchun sample from the Survey on Foreign Residents in China (SFRC 2017–2019) to examine the influence of social networks and social engagement on settlement intentions. It also considered differences in the classification of social networks and engagement strength, as well as classification by country of origin. This study identified that social networks and social engagement in the destination country play an essential role in the willingness of high skilled migrants to stay in Changchun. Additionally, international enclaves negatively affected their willingness to stay. Furthermore, the relative strength of migrants’ social networks and social engagement in the destination country exerted varying effects on the intensity of their settlement intentions. That is, using high skilled migrants with strong Chinese social networks and social engagement as the reference group, relying solely on a strong social network in China while lacking social engagement significantly reduced their willingness to settle. A weak social networks and low social engagement also significantly decreased their willingness to settle. Moreover, settlement intentions of the high skilled migrants differed significantly by country of origin. If we selected the same reference term, the willingness of expatriates from developed countries to stay decreased significantly. In the sections concerning comparison and robustness checks, national data were employed (SFRC 2019). Highly skilled expatriates in Guangzhou, Hangzhou, and Yiwu demonstrated the synergistic interaction between ethnic communities and work units (danwei), whereas those in Changchun exhibited a certain uniqueness, embedding themselves in Chinese society through their own human capital and danwei affiliations.